Physical Model for the Current-Voltage Hysteresis and Impedance of Halide Perovskite Memristors - Berruet, Mariana (2022)
An investigation of the kinetic behavior of MAPbI3 memristors shows that the onset voltage to a high conducting state depends strongly on the voltage sweep rate, and the impedance spectra generate complex capacitive and inductive patterns. We develop a dynamic model to describe these features and obtain physical insight into the coupling of ionic and electronic properties that produce the resistive switching behavior. The model separates the memristive response into distinct diffusion and transition-state-formation steps that describe well the experimental current-voltage curves at different scan rates and impedance spectra. The ac impedance analysis shows that the halide perovskite memristor response contains the composition of two inductive processes that provide a huge negative capacitance associated with inverted hysteresis. The results provide a new approach to understand some typical characteristics of halide perovskite devices, such as the inductive behavior and hysteresis effects, according to the time scales of internal processes.